2023
DOI: 10.1113/ep089686
|View full text |Cite
|
Sign up to set email alerts
|

Barosensory vessel mechanics and the vascular sympathetic baroreflex: Impact on blood pressure homeostasis

Abstract: New Findings What is the topic of this review? We review barosensory vessel mechanics and their role in blood pressure regulation across the lifespan. What advances does it highlight? In young normotensive men, aortic unloading mechanics contribute to the resting operating point of the vascular sympathetic baroreflex; however, with advancing age, this contribution is removed. This suggests that barosensory vessel unloading mechanics are not driving the well‐documented age‐related increase in resting muscle sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…to poorer baroreceptor function in later life. Their review (Hughes et al, 2023) discusses how recent advancements in vascular ultrasound methods can be used to quantify parameters of baroreceptor function, such as rate of unloading and time spent unloaded. Using these novel techniques, Lord et al (2020) found that baroreceptor unloading mechanics were indeed altered in older age, with a reduced rate of unloading and less time spent unloaded observed in older versus younger healthy males.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…to poorer baroreceptor function in later life. Their review (Hughes et al, 2023) discusses how recent advancements in vascular ultrasound methods can be used to quantify parameters of baroreceptor function, such as rate of unloading and time spent unloaded. Using these novel techniques, Lord et al (2020) found that baroreceptor unloading mechanics were indeed altered in older age, with a reduced rate of unloading and less time spent unloaded observed in older versus younger healthy males.…”
mentioning
confidence: 99%
“…Recent work by Rachel Lord and colleagues has provided insight into whether the age‐related rise in sympathetic nerve activity is related to poorer baroreceptor function in later life. Their review (Hughes et al., 2023 ) discusses how recent advancements in vascular ultrasound methods can be used to quantify parameters of baroreceptor function, such as rate of unloading and time spent unloaded. Using these novel techniques, Lord et al.…”
mentioning
confidence: 99%